Research on Wildlife Protection and Nature Reserve Management - Ji, Hengfang (International Journal of Natural Resources and Environmental Studies, 2024)
As an important part of modern environmental protection, wildlife protection and reserve management are of great significance to maintain the ecological balance and biodiversity of the earth. In today ’s increasingly serious global environmental problems, especially climate change, habitat destruction, and species extinction, wildlife and its habitat protection have become a hot issue of concern to the international community. Governments, non-governmental organizations and the community to actively participate in, and actively promote the protection of the ecological environment for future generations to create a good ecological environment.